2023
DOI: 10.3390/ijfs11020071
|View full text |Cite
|
Sign up to set email alerts
|

A Decade of Cryptocurrency Investment Literature: A Cluster-Based Systematic Analysis

Abstract: This study aims to systematically analyze and synthesize the literature produced thus far on cryptocurrency investment. We use a systematic review process supported by VOSviewer bibliographic coupling to review 482 papers published in the ABS 2021 journal list, considering all different areas of knowledge. This paper contributes an in-depth systematic analysis on the unconsolidated topic of cryptocurrency investment through the use of a cluster-based approach grounded in a bibliographic coupling analysis, reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 104 publications
(101 reference statements)
0
4
0
Order By: Relevance
“…Moreover, the territorial distribution seems adequate, as the points on the map coincide with the most important cities in the country. Although it could be criticized here that, if one of the objectives of establishing bitcoin as legal tender is to improve financial inclusion, it is leaving aside underdeveloped areas, where financial inclusion is less guaranteed (Mota Makore et al, 2023;Almeida & Gonçalves, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the territorial distribution seems adequate, as the points on the map coincide with the most important cities in the country. Although it could be criticized here that, if one of the objectives of establishing bitcoin as legal tender is to improve financial inclusion, it is leaving aside underdeveloped areas, where financial inclusion is less guaranteed (Mota Makore et al, 2023;Almeida & Gonçalves, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the existing statistical data, it can be observed that the renewable energy sector has exhibited the most substantial growth rate over the last twenty years. According to Almeida & Gonçalves (2023) and Sial (2022), renewable sources accounted for 20.1% of global power generation and 19.9% of total energy consumption in the year 2021.…”
Section: Environmental Attention and Green Cryptocurrencymentioning
confidence: 99%
“…Hence, examining the impact of Bitcoin's ecological principles on sustainable financial systems is imperative. The existing body of research indicates that the environmental concerns associated with cryptocurrency lack empirical evidence to substantiate their claims (Almeida & Gonçalves, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The code enabling operations, however, was released in 2009. In this way, cryptocurrencies, since those years, have been conceived as a new possibility within innovative payment mechanisms and their growth within the virtual payment market has been such that it has generated a previously unknown financial dilemma, in which banks and other types of intermediaries no longer have within their reach the total control of the payment flow market (Álvarez-Díaz 2019; Almeida and Gonçalves 2023). As virtual, decentralized, and independent currencies, they have presented a progressive growth but been very volatile in terms of value as a consequence of the effect caused by speculations (Vučinić and Luburić 2022;Portugal Duarte et al 2023).…”
Section: Introductionmentioning
confidence: 99%